1993
DOI: 10.1007/bf01203283
|View full text |Cite
|
Sign up to set email alerts
|

Fundus pigmentation and the electroretinographic luminance-response function

Abstract: Dark-adapted and light-adapted electroretinographic luminance-response functions were recorded from subjects with light or dark fundus pigmentation based on digitized fundus photographs. For dark- and light-adapted electroretinograms, subjects with dark fundi had smaller b-wave amplitudes at all luminance levels. There was no significant difference in b-wave implicit time for the dark-adapted electroretinogram, but there was a significant difference for the light-adapted ERG between the two groups. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 8 publications
3
14
2
Order By: Relevance
“…Our findings that some ERGs are larger from those with lighter eyes are in keeping with previous studies [2][3][4][5][6][7]. The ITs were earlier for the blue group compared with the brown group for most of ERG components, both dark-and lightadapted, which may suggest that a basic process, such as the phototransduction cascade, may be slightly accelerated in those with blue eyes.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings that some ERGs are larger from those with lighter eyes are in keeping with previous studies [2][3][4][5][6][7]. The ITs were earlier for the blue group compared with the brown group for most of ERG components, both dark-and lightadapted, which may suggest that a basic process, such as the phototransduction cascade, may be slightly accelerated in those with blue eyes.…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported that human eyes with lighter fundi demonstrate larger full-field ERGs under both light-and dark-adapted conditions with normal or supranormal amplitudes in those with albinism [2][3][4][5][6][7]. Fundus pigmentation corresponds closely to iris pigmentation, iris colour and skin pigmentation [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smaller b-wave amplitudes were found in patients with higher fundus pigmentation, which led to the hypothesis that this decrease could be related to a higher ocular resistance caused by melanin [52,53]. Russell-Eggitt et al [44] recorded ERGs in ocular and oculocutaneous albino Fig.…”
Section: Figmentioning
confidence: 96%
“…As a consequence of the reduced number of rods, an impaired post-receptoral response would also be expected. On the other hand, there are several reports that ERG amplitudes are larger in albino humans [44,[51][52][53]. Therefore, the purpose of this study was to compare the single aspects of retinal function of two closely related strains of pigmented and albino rats by comparing several ERG parameters.…”
Section: Introductionmentioning
confidence: 96%